Exemplarische Integration raumrelevanter Indikatoren auf Basis von "Fernerkundungsdaten" in das Sozio-oekonomische Panel (SOEP) - Jan Goebel; Gert G. Wagner; Michael Wurm (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
– This paper demonstrates spatial evaluation methods on data from the German Socio-Economic Panel (SOEP) study using geo-coordinates and spatially relevant indicators from remote sensing data. By geocoding the addresses of private households (while not identifying them by name and while guaranteeing their complete anonymity) with block-level geographic precision, respondents' data can now be analyzed in a specific spatial context. Previous regionalanalyses of SOEP on the basis of official regional indicators (e.g., the unemployment rate) were always confronted with very imprecise spatial information. This limitation has now been overcome with the geocoded respondents' information. Within the protected unit of the fieldwork organization responsible for SOEP (TNS Infratest, Munich), the addresses of survey households are used to generate a variable describing the location of the household with block-level precision. At DIW Berlin, this additional variable is fed into a special computer infrastructure with multiple security layers that makes the socio-economic analysis possible. This paper demonstrates the use of geographical location and remote sensing data in checking respondents' subjective assessments of the location of their residence. The analytical potential of linking remote sensing data and survey data is demonstrated and discussed.
Keywords: C81; C83; R14; 330; remote sensing data; social sciences; economics; behavioral sciences; multi-disciplinarity; SOEP; Panel; Privater Haushalt; Geographie; Region; Satellitenkommunikation; Deutschland